2012
DOI: 10.1063/1.3675508
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical strain microscopy with blocking electrodes: The role of electromigration and diffusion

Abstract: Electrochemical strains are a ubiquitous feature of solid state ionic devices ranging from ion batteries and fuel cells to electroresistive and memristive memories. Recently, we proposed a scanning probe microscopy (SPM) based approach, referred as electrochemical strain microscopy (ESM), for probing local ionic flows and electrochemical reactions in solids based on bias-strain coupling. In ESM, the sharp SPM tip concentrates the electric field in a small (10-50 nm) region of material, inducing interfacial ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 64 publications
1
31
0
Order By: Relevance
“…This suggests two important limits, namely a high frequency regime where diffusion length is smaller than the tip radius and process is essentially 1D, and a low frequency regime where the spatial extent of affected region diverges with time. ESM was extended to regimes with both diffusive and migration transport for open and blocking 259 electrodes, giving rise to more complex time dispersion of responses. 289,328 The important aspect of pure Vegard mechanisms is that it does not predict the formation of remnant states with opposite electromechanical responses and hysteresis loops beyond kinetic ones.…”
Section: Ferroelectric Switchingmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests two important limits, namely a high frequency regime where diffusion length is smaller than the tip radius and process is essentially 1D, and a low frequency regime where the spatial extent of affected region diverges with time. ESM was extended to regimes with both diffusive and migration transport for open and blocking 259 electrodes, giving rise to more complex time dispersion of responses. 289,328 The important aspect of pure Vegard mechanisms is that it does not predict the formation of remnant states with opposite electromechanical responses and hysteresis loops beyond kinetic ones.…”
Section: Ferroelectric Switchingmentioning
confidence: 99%
“…248,257 The original description of ESM mechanism considered purely diffusional dynamics with fast voltage controlled generation-recombination of ionic species on the surface and near surface regions. 258 Subsequently, the model was extended to include both migration transport [259][260][261] and electrostrictive effects. 118,262,263 Finally, it was shown that ESM mechanism can be present even in the absence of a surface reaction.…”
Section: B Electrochemical Strain Microscopy (Esm)mentioning
confidence: 99%
“…The present work is based on reusing the formal description of Bohn et al, 19 which is very similar to previous works done on ESM modeling, 3,10,20 and will also compare the influence of D eff on the ESM signal. The objective is to model the time evolution of lithium concentration, surface displacement, and the ESM signal below the tip during and after DC pulses.…”
Section: Introductionmentioning
confidence: 89%
“…They suggested that the produced electrochemical strain is mediated by the local transport mechanisms controlled (among others) by the ionic diffusivity D d . Later Morozovska et al 10 used this concentration-change based model in order to uncover the image formation mechanisms for systems with ion-blocking electrodes and without local electroneutrality. They computed values for two lithium host materials: LiCoO 2 and LiMn 2 O 4 , and showed a displacement much lower than 1 pm for frequencies above 10 4 Hz even though a relatively high diffusion coefficient of 10 13 m 2 s 1 was used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation